Gastroduodenal Outlet Obstruction and Palliative Self-Expandable Metal Stenting: A Dual-Centre Experience. (10th November 2013) - Ding, Nik S.; Alexander, Sina; Swan, Michael P.; Hair, Christopher; Wilson, Patrick; Clarebrough, Emma; Devonshire, David
Abstract : Background . Self-expandable metal stents (SEMs) are increasingly being utilised instead of invasive surgery for the palliation of patients with malignant gastroduodenal outlet obstruction. Aim . To review two tertiary centres' experience with placement of SEMs and clinical outcomes. Methods . Retrospective analysis of prospectively collected data over 12 years. Results . Ninety-four patients (mean age, 68; range 28–93 years) underwent enteral stenting during this period. The primary tumour was gastric adenocarcinoma in 27 (29%) patients, pancreatic adenocarcinoma in 45 (48%), primary duodenal adenocarcinoma in 8 (9%), and cholangiocarcinoma and other metastatic cancers in 14 (16%). A stent was successfully deployed in 95% of cases. There was an improvement in gastric outlet obstruction score (GOOS) in 84 (90%) of patients with the ability to tolerate an enteral diet. Median survival was 4.25 months (range 0–49) without any significant differences between types of primary malignancy. Mean hospital stay was 3 days (range 1–20). Reintervention rate for stent related complications was 5%. Conclusion . The successful deployment of enteral stents achieves excellent palliation often resulting in the prompt reintroduction of enteral diet and early hospital discharge with minimal complications and reintervention.